The Effect Of Pesantren Environment And Teacher Competency Of The Formation Of Santri Character Of Pesantren Routlotul Muta'alimin 2 In Accordance And Community Development In Malangbong District, Garut District - Effendi, Wiwit Yuhita; Marlina, Lina (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2020)
ABSTRACT Supervision of pesantren is important so that curriculum in pesantren can keep up with the changing times. Roudlotul Muta'alimin 2 Islamic Boarding School is one of the most prominent Islamic boarding schools in Malangbong, Garut Regency. In order to maintain its existence, the pesantren will strive for the learning environment in the pesantren and the competence of its teachers to be in line with the expectations of the community, which in turn will lead to the formation of the personal character of Islamic students and can follow the changing times. The purpose of this study is to find out the influence of the Islamic Boarding School Environment and Teacher Competence on the Character Building of Roudlotul Muta'alimin 2 Islamic Boarding School students' character in community development in Malangbong District, Garut Regency. This research uses a quantitative approach with multiple regression analysis. Data collection using a questionnaire. The research respondents were 140 students using simple random sampling techniques. The results showed that simultaneously or partially the Islamic Boarding School Environment and Teacher Competence had a significant effect on Character Building. In addition, the Pesantren Environment and Teacher Competence contributed 84.2% of the effect on Character Building, while the remaining 15.8% was the influence of other variables not examined. Keywords: Islamic Boarding School Environment, Teacher Competence, Character Building, Community Development.